2012
DOI: 10.1063/1.3693123
|View full text |Cite|
|
Sign up to set email alerts
|

Nonlinear kinetic modeling of stimulated Raman scattering in a multidimensional geometry

Abstract: In this paper, we derive coupled envelope equations modeling the growth of stimulated Raman scattering (SRS) in a multi-dimensional geometry and accounting for nonlinear kinetic effects. In particular, our envelope equations allow for the nonlinear reduction of the Landau damping rate, whose decrease with the plasma wave amplitude depends on the rate of side-loss. Account is also made of the variations in the extent of the plasma wave packet entailed by the collisionless dissipation due to trapping. The dephas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…Thus, we can write ∆h = 2εv 2 φ u Q θ , Var(∆h) = 2εv 2 φ uVar(Q) (17) where u and Q are evaluated at z = z R . We calculate analytical changes of energy due to scattering (17) and numerical changes.…”
Section: B Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we can write ∆h = 2εv 2 φ u Q θ , Var(∆h) = 2εv 2 φ uVar(Q) (17) where u and Q are evaluated at z = z R . We calculate analytical changes of energy due to scattering (17) and numerical changes.…”
Section: B Scatteringmentioning
confidence: 99%
“…Assuming that the wave spectrum is wide enough and the wave intensity is sufficiently low, one can model the wave-particle resonant interactions using quasi-linear theory [4][5][6][7] generalized for systems with inhomogeneous magnetic field and background plasma [8,9]. However, various recent spacecraft observations in the near-Earth plasma environment [10][11][12][13][14], laboratory experiments [15,16], and inertial confinement fusion simulations and experiments [17][18][19] have demonstrated that the applicability of quasi-linear theory is often questionable, because electrons happen to interact with coherent waves sufficiently intense to significantly influence electron motion over long time intervals. There are two main effects of such nonlinear wave-particle interactions: particle trapping by the waves (phase trapping) and particle scattering (phase bunching) with nonzero average change of particle energy [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…To cite a few examples, the EPW may by subjected to secondary instabilities leading to the growth of sidebands [42][43][44], so that, except in some special instances [45,46], the total electrostatic field, E(x, t, ψ), is no longer a slowlyvarying function of x and t (at fixed ψ). Moreover, due to the amplitude dependence of the wave frequency, the wave front may bend so as to make the EPW self-focus [28,38], which, again, renders the assumption of a slowly-varying amplitude no longer valid. In the situation, observed both numerically and experimentally [38,48], when wavefront bowing is followed by the growth of sidebands, the phase modulation due to the transverse variations of the wave amplitude is negligible compared to that due to the space dependence of the nonlinear frequency shift.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-D version of this code was used in Ref. [28] to predict when the EPW would self-focus and, again, saturate SRS, with predictions on Raman reflectivity comparing even better with experiment [50] than those from PIC codes [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation